PERISTILAHAN TATA BOGA DAYAK SIMPAKNG DI KECAMATAN SIMPANG HULU KABUPATEN KETAPANG - Yohanes Krisostomus; Laurensius Salem; Agus Syahrani (Universitas Tanjungpura, 2021)
AbstractCulinary has become one of the attractions of the Simpakng Dayak community,especially Simpang Hulu, current events, such as custom events. This study aimsto describe the form of terminology, lexical meanings, cultural meanings relatedto Simpakng Dayak culinary, and to implement them into the Procedure Textmaterial for Bahasa Indonesia subject grade VII Curriculum 2013. This study useda qualitative descriptive method. The research subjects are speakers of the DayakSimpakng language, Simpang Hulu District, District of Simpang Hulu, Ketapangregency, aged 20-65 years (not senile). Data collection techniques used arepancing, cakap, note-taking, and recording techniques. In data analysis, the datafrom the four techniques were transcribed, translated into Indonesian, classified,and taken into conclusions. Based on the analysis, there are 30 terms used in theSimpakng Dayak culinary. Fourteen terms relate to ingredients and spices, andtwelve terms relate to serving method. These terms are classified into three forms,namely monomorphemic, polymorphemic, and phrase. In the implementation ofteaching materials, these culinary terms are integrated into the procedural textmaterial in Bahasa Indonesia subject.Keywords: Terminology, Culinary, Dayak Simpakng